Ortega Without Weimar - Quintanilla Navarro, Ignacio (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2013)
Between 1935 and 1951 Ortega wrote almost nothing about technology. This silence is analized form the point of view of “La Idea de Principio en Leibniz”. The conclusion is that Ortega returns to a productive-pragmatic interpretation of the human live as ejecution –like the expressed in the “Meditación de la técnica”– when he needs to take distance from Heidegger. This argumental line, forgotten in the 30s, is taken again in the 50s, with a project of modal ontology, also frustrated. In this project, the question for the possibility of the being appears more radical than the question for the being himself. This work tries to reconstruct the argumentation that Ortega does not complete and to justify the exemplary value that has this event in order to understand the situation of the philosophy oftechnology at the present.